Encapsulation of Co3O4 Nanocone Arrays via Ultrathin NiO for Superior Performance Asymmetric Supercapacitors. Issue 48 (4th November 2020) - Adhikari, Sangeeta; Selvaraj, Seenivasan; Ji, Su‐Hyeon; Kim, Do‐Heyoung
Abstract: Designing of multicomponent transition metal oxide system through the employment of advanced atomic layer deposition (ALD) technique over nanostructures obtained from wet chemical process is a novel approach to construct rational supercapacitor electrodes. Following the strategy, core–shell type NiO/Co3 O4 nanocone array structures are architectured over Ni‐foam (NF) substrate. The high‐aspect‐ratio Co3 O4 nanocones are hydrothermally grown over NF following the precision controlled deposition of shell NiO considering Co3 O4 nanocone as host. NiO thickness of 5 nm exhibits the highest specific capacity of 1242 C g −1 (2760 F g −1 ) at current density 2 A g −1, which is greater than pristine Co3 O4 @NF (1045.8 C g −1 or 2324 F g −1 ). The rate capability with 5 nm NiO/Co3 O4 @NF nanocone structures is about 77% whereas Co3 O4 @NF retains 46 % of capability at 10 A g −1 . The ultrathin ALD 5 nm NiO accelerates both rate capability and 95.5% cyclic stability after 12 000 charge–discharge cycles. An asymmetric device fabricated between 5 nm NiO/Co3 O4 @NF (positive) || activated carbon (negative) achieves an energy density of 81.45 Wh kg −1 (4268 W kg −1 ) with good cycling device stability. Additionally, LEDs can be energized by two ASC device in series. This work opens the path in both advanced electrode material and surface modification of earth‐abundant systems for efficient and real‐time supercapacitor applications. Abstract : Atomic layer deposited ultrathin NiO films over Co3 O4 nanocone structures to achieve core–shell design are presented here. Optimized ultrathin films of 5 nm NiO on Co3 O4 enhance the rate capability and capacity retention. Synergistic performance due to surface passivation of Co3 O4 with collective reactivity from atomic layer deposition NiO. Long‐term stability and high energy density is achieved with 5 nm NiO/Co3 O4 @NF||AC ASC device.